Evaluation of impairment in fine motor skills in patients with major depressive disorder: Major depressive disorder and fine motor skills - Kılıçaslan Şahin, Emine Hande; Koçak, Orhan Murat; Şahin, Oruç (Journal of Surgery and Medicine, 2024)
Background/Aim: Major Depressive Disorder (MDD) is a prevalent psychiatric condition linked to chronic conditions, suicide and relapse, leading to disability. Fine motor skills (FMS) can potentially provide valuable insights into the suspected psychomotor slowing associated with depression. This experimental, observational study aims to use a fresh paradigm to probe how the slowing of FMS impacts MDD patients, particularly in relation to motor and cognitive processes. Methods: This study involved 28 patients with MDD and 28 healthy control subjects. We developed the Serial Reaction Time Task (SRTT), Finger Tapping Test (FTT), and Target Hitting Test (THT) to examine the impact on FMS in relation to motor and cognitive processes. The THT incorporates cognitive elements like strategy and action monitoring and assimilates the other two tests. Participants were asked to complete the SRTT, FTT, THT, Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) in two separate sessions. Results: We found significant differences between the groups across BDI, BAI, FTT, and SRTT data (P<0.001 for BDI, BAI, P=0.019 for FTT, P=0.032 for SRTT). There was also a noticeable difference in THT performance among the groups (P=0.013). The disparity between the depression group and the control group was primarily attributed to the THT error score (P=0.003). We noted that when BDI and SRTT scores increased, THT target values decreased (P=0.001 and P<0.001, respectively), but they increased with higher FTT scores (P<0.001). The depression group performed worse than the control group on all three computerized tests related to FMS (SRTT, FTT, THT). The poorer performance of patients with depression in THT was mostly due to THT error values. This suggests that these patients may have exerted more effort on motor performance to hit the target, compensating with physical effort rather than applying the necessary cognitive strategy required by the test. Conclusion: This study’s findings indicate that MDD primarily impacts cognitive functions while also impairing FMS.